Methods of Extracting Feature from Photoplethysmogram Waveform for Non-Invasive Diagnostic Applications - Hafifah, Ab Hamid; Nazrul Anuar, Nayan (International Journal of Online and Biomedical Engineering (iJOE), 2020)
This paper presents a bibliographical survey of recently-published research on different techniques to extract feature from photoplethysmogram (PPG). These techniques and approaches have been implemented for better accuracy in detecting diseases. Moreover, several aspects in analyzing PPG waveform are discussed on the techniques in feature extraction, parameters involved and performance comparisons. This review will serve as a comparative study and reference for researches working on PPG waveform in health care applications.